Ratio of the value of the blood pressure and myocardial ischemia in critical patients over 65 years old - Barrios-Morocho, Juan Luis (2016)
Objective: To know the relationship between the values of the pressure blood and myocardial ischemia in critical patients older than 65 years who were admitted in emergency to a hospital of medium complexity of social security. Material and methods: Cross-sectional, retrospective, explanatory and observational study. Sampling not probabilistic in 192 critical patients (priority I and II), older than 65 years, which were admitted by emergency to the Hospital II Vitarte EsSalud, since January 2014 to October 2015, with at least one determination of Troponin I at admission in emergency. Ranges of Spearman correlation Test and Test of binary logistic were used to calculate the risk of occurrence of myocardial ischemia in relation to systolic or diastolic blood pressure values. Results: There was a negative correlation between the value of the diastolic blood pressure with the presence of ischemia myocardial (Rho of Spearman = - 0,155; p = 0,032), statistically significant. It was risk found risk of ischemia myocardial in patients with diastolic hypotension OR: 2,545; IC: 1,051-6,163; NC: 95%; and with normal OR diastolic pressure values: 3,320; IC: 1,479-7,452; NC: 95%. Conclusions: Changes in blood pressure are usually presented in critically ill patients, having to take into account the assessment of cardiac enzymes, when diastolic blood pressure values are below normal values. Although the results are clearly predictive, they can't be generalized given our non-random sample, and restricted to over 65 years old.